Solve for x
x=\frac{\sqrt{138}}{12}\approx 0.97894501
x=-\frac{\sqrt{138}}{12}\approx -0.97894501
Graph
Share
Copied to clipboard
\frac{15}{100}\times 9600x^{2}=1380
Multiply both sides of the equation by 3.
\frac{3}{20}\times 9600x^{2}=1380
Reduce the fraction \frac{15}{100} to lowest terms by extracting and canceling out 5.
1440x^{2}=1380
Multiply \frac{3}{20} and 9600 to get 1440.
x^{2}=\frac{1380}{1440}
Divide both sides by 1440.
x^{2}=\frac{23}{24}
Reduce the fraction \frac{1380}{1440} to lowest terms by extracting and canceling out 60.
x=\frac{\sqrt{138}}{12} x=-\frac{\sqrt{138}}{12}
Take the square root of both sides of the equation.
\frac{15}{100}\times 9600x^{2}=1380
Multiply both sides of the equation by 3.
\frac{3}{20}\times 9600x^{2}=1380
Reduce the fraction \frac{15}{100} to lowest terms by extracting and canceling out 5.
1440x^{2}=1380
Multiply \frac{3}{20} and 9600 to get 1440.
1440x^{2}-1380=0
Subtract 1380 from both sides.
x=\frac{0±\sqrt{0^{2}-4\times 1440\left(-1380\right)}}{2\times 1440}
This equation is in standard form: ax^{2}+bx+c=0. Substitute 1440 for a, 0 for b, and -1380 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{0±\sqrt{-4\times 1440\left(-1380\right)}}{2\times 1440}
Square 0.
x=\frac{0±\sqrt{-5760\left(-1380\right)}}{2\times 1440}
Multiply -4 times 1440.
x=\frac{0±\sqrt{7948800}}{2\times 1440}
Multiply -5760 times -1380.
x=\frac{0±240\sqrt{138}}{2\times 1440}
Take the square root of 7948800.
x=\frac{0±240\sqrt{138}}{2880}
Multiply 2 times 1440.
x=\frac{\sqrt{138}}{12}
Now solve the equation x=\frac{0±240\sqrt{138}}{2880} when ± is plus.
x=-\frac{\sqrt{138}}{12}
Now solve the equation x=\frac{0±240\sqrt{138}}{2880} when ± is minus.
x=\frac{\sqrt{138}}{12} x=-\frac{\sqrt{138}}{12}
The equation is now solved.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}